PENGARUH ARUS KAS BEBAS, CAPITAL ADEQUACY RATIO DAN GOOD CORPORATE GOVERNANCE PADA MANAJEMEN LABA - Yogi, Luh Made Dwi Parama; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2016)
The aim of this study was to obtain empirical evidence about the influence of free cash flow, capital adequacy ratio and good corporate governance (GCG) in earnings management. This research was conducted on banking companies listed on the Indonesia Stock Exchange, with a period of research from 2010-2014. Results of testing the hypothesis by using multiple linear regression analysis proved that free cash flow has negative effect on earnings management. Capital adequacy ratio has positive effect on earnings management. Proxy of GCG by the independent board, audit committee, managerial ownership and institutional ownership has no effect on earnings management.
Keywords: earnings management, free cash flow, CAR and GCG